Research methods in psychology - Shaughnessy, John J. (McGraw-Hill, c2006., 2006)
Considered one of the best undergraduate method texts in the field for the past two decades, Research Methods in Psychology captures the excitement of psychological inquiry as well as the importance of understanding the methodology that is used to conduct research. The text has been praised for its clear writing, logical organization, depth of coverage, and wide variety of examples from different fields of psychology. The new edition includes updated research, a thoroughly revised introductory chapter, and improved pedagogical features designed to enhance students' learning.